Correlation Between the Evolution of Somatic Alterations During Lymphatic Metastasis and Clinical Outcome in Penile Squamous Cell Carcinoma - Cao, Jian; Yang, Chun-He; Han, Wei-Qing; Xie, Yu; Liu, Zhi-Zhong; Jiang, Shu-Suan (Frontiers in Oncology, 2021)
Penile squamous cell carcinoma (PSCC) is a rare malignancy with poor survival after standard treatment. Although genomic alterations of PSCC have been characterized in several latest studies, the association between the formation of somatic landscape and regional lymph node metastasis (LNM), an important predictor for patient survival, has not been comprehensively investigated. Here, we collected formalin-fixed paraffin-embedded tumor tissue and matched normal samples of 32 PSCC patients, including 14 LNM patients and 18 clinically node-negative patients, to implement a whole-exome sequencing. Comparison of genomic features among different lymph node status subgroups was conducted after genomic profiling and its effects on patient survival were explored. Top-ranked recurrent gene mutants in our PSCC cohort were TP53 (13/32), NOTCH1 (12/32), CDKN2A (11/32), TTN (9/32) and FAT1 (8/32), mainly identified in the Notch, Hippo, cell cycle, TP53, RTK-RAS and PI3K pathways. While CDKN2A was confirmed to be the driver gene in all PSCC patients, certain gene mutants were significantly enriched in LNM involved patients, including TP53 (9/14 vs. 4/18, p = 0.029) and GBF1 (4/14 vs. 0/18, p = 0.028). Overall survival stratification of PSCC patients were found to be significantly correlated with mutations of three genes, including PIK3CA (Hazard ratio [HR] = 4.15, p = 0.029), CHD7 (HR = 4.82, p = 0.032) and LAMC3 (HR = 15.9, p < 0.001). PIK3CA and LAMC3 held a higher prevalence in patients with LNM compared to those without LNM (PIK3CA: 3/14 vs. 1/18, LAMC3: 2/14 vs. 1/18). Our finding demonstrated that genomic divergence exists across PSCC patients with different lymph node statuses, and it may be correlated with their survival outcome. It helps delineate somatic evolution during tumor progression and perfect potential therapeutic intervention in this disease.